Pengaruh lingkungan sekolah terhadap pembentukan identitas muslim: Studi kasus tentang internalisasi nilai-nilai agama Islam - kamilah, Rohmatul; Ghozi, Ahmad; Izzatunnisa, Alifa; Hibbatulloh, M. Fawwas (Maliki Interdisciplinary Journal, 2024)
The research uses a literature review research method, where this research examines the impact of the school environment on the internalization of Islamic values ​​and the formation of Muslim identity among students. Data was collected from 30 students and 10 teachers at a private Islamic school in Indonesia. The findings show that a supportive and inclusive school environment plays an important role in shaping their internalization of Islamic values ​​and Muslim identity. Students who attend schools with a strong Islamic atmosphere and sense of community are more likely to internalize values ​​such as love, empathy, and kindness, as well as develop a strong sense of identity as Muslims. The research results show that the school environment can facilitate or hinder the process of internalizing Islamic values ​​and forming Muslim identity. A supportive school environment can create a sense of belonging and comfort among students, making them feel more confident in their faith and more likely to adopt Islamic values. Conversely, an unsupportive or hostile environment can create feelings of isolation and exclusion, making it difficult for students to internalize Islamic values ​​and form a strong sense of Muslim identity. The findings of this study have implications for educators and policymakers who seek to foster positive and inclusive school environments that support the development of Muslim students' identities and beliefs.